A Perspective on Multi-target Drugs for Alzheimer's Disease - Benek, Ondrej; Korabecny, Jan; Soukup, Ondrej (Trends in pharmacological sciences, 2020)
Alzheimer's disease (AD) has a complex pathophysiology that includes aggregation of pathological proteins, impaired neurotransmission, increased oxidative stress, or microglia-mediated neuroinflammation. Therapeutics targeting only one of these AD-related subpathologies have not yet been successful in the search for a disease-modifying treatment. Therefore, multi-target drugs (MTDs) aiming simultaneously at several subpathologies are expected to be a better approach. However, the concept of MTD is inherently connected with several limitations, which are often ignored during MTD design and development. Here, we provide an overview of the MTD approach and discuss its potential pitfalls in the context of AD treatment. We also put forward ideas to be used in the rational design of MTDs to obtain drugs that are effective against AD.
Keywords: Synaptic Transmission; oxidační stres; polypharmacology; Pharmaceutical Preparations; Inflammation; multi-target drugs; Alzheimer’s disease; Alzheimerova nemoc; Alzheimer Disease; drug design; nervový přenos; zánět; léčivé přípravky; Drug Delivery Systems; lidé; Humans; Oxidative Stress; designed multiple ligands; lékové transportní systémy